Synthesis, characterization, and antibacterial activity of azodyes incorporated acridine chromophore and their applications in polyester printing - Khalid Hassan (Growing Science, 2022)
A series of azo dyes incorporated acridine chromophore labelled as 8 (a-d), 10 (a, b), 12 and 14 were prepared in very good yields starting from 9-chloroacridine 1 followed by amination, diazotization and coupling either with rhodanine analogues 6 (a, b) or other coupling partners 9 (a, b), 11 and 13. FT-IR, 1H NMR, and mass spectroscopic analysis were used to establish the structures of the produced azo dispersed dyes. Moreover, the synthesized azo dyes were used to prepare pastes that were used to print polyester fabric using classic silk-screen printing techniques. The dyes were tested for color strength and fastness properties, and they showed good fastness resistance to washing, rubbing, and perspiration, as well as fastness to sublimation and light. The dyes were further screened for their in vitro antibacterial activity against both Gram (+) and Gram (-) bacterial species. Most of them showed promising activities against these tested organisms.